HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG ANEMIA DI AKBID MARDI RAHAYU KABUPATEN SEMARANG - Mularsih, Sri; Zulfa, Maulida (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Adolescence is the age period that occurs after childhood ends, characterized by rapid physical growth. Anemia is a global nutritional problem, especially in developing countries, including Indonesia. The rate of iron deficiency anemia in Indonesia is 72.3%. Iron deficiency in adolescents results in paleness, weakness, fatigue, dizziness, and decreased concentration in learning. Causes include: parental education level, economic status, adolescent girls' knowledge of anemia, iron and vitamin C consumption, and menstrual duration). The prevalence of anemia in Indonesia is 26.50% among adolescent girls, 26.9% among women of childbearing age, 40.1% among pregnant women, and 47.0% among toddlers. The purpose of this study was to analyze adolescent girls' knowledge and attitudes toward anemia.This study used a cross-sectional design. The sampling technique used was saturated sampling, or total sampling, which involves taking all members of the population as samples.The results of this study indicate a relationship between adolescent girls' knowledge and attitudes about anemia, with a chi-square test yielding a p-value of 0.002 <0.05.